PELATIHAN MEDIA INTERAKTIF BAMBOOZLE UNTUK MAHASISWA SEBAGAI CALON GURU - Dinaloni, Diah; Muktiadji, Henky; Kurniawan, Dandi (Yayasan Education and Social Center, 2025)
The development of information and communication technology has changed the way teachers feliver material anf the way students receive learning. The learning process is now required to be more interactive, creative, and aligned with the characteristics of the digital generation. One technology that can be utilized in learning is the Bamboozle application. Bamboozle is a game-based learning platform that allows teachers to present material in the form of interactive quizzes. With its simple yet engaging features, Bamboozle can be used to: (1) Test students’ understanding directly; (2) Create an enjoyable learning atmosphere; and (3) Develop critical and collaborative thinking skills. Although Bamboozle offers many benefits, the reality is that many students: (1) Are not yet familiar with the use of technology-based interactive media; (2) More often use conventional methods in learning simulations; and (3) Are less trained in integrating digital media with the curriculum and local values. Based on this, training on the interactive learning media Bamboozle becomes important to implement. Training on the interactive learning media Bamboozle for prospective teacher students has had a positive impact on improving technology-based pedagogical competence. This training activity is considered successful because: (1) It equips students with practical knowledge and skills in using Bamboozle as a learning medium; (2) It enhances students’ creativity in designing interactive quizzes relevant to the courses and curriculum; (3) It fosters students’ motivation and enthusiasm to integrate technology into the learning process; and (4) It prepares students as future teachers who are adaptive to technological developments and the needs of learner in the digital era. Thus, this training contributes significantly to preparing prospective teachers to be professional, innovative, and capable of delivering enjoyable and meaningful learning experiences.